Inhibition of hippocampal interleukin-6 receptor-evoked signalling normalises long-term potentiation in dystrophin-deficient mdx mice - Kimberley A. Stephenson; Aaron Barron; Mark G. Rae; Dervla O'Malley (Brain, Behavior, & Immunity - Health)
Duchenne muscular dystrophy (DMD), an X-linked neuromuscular disorder, characterised by progressive immobility, chronic inflammation and premature death, is caused by the loss of the mechano-transducing signalling molecule, dystrophin. In non-contracting cells, such as neurons, dystrophin is likely to have a functional role in synaptic plasticity, anchoring post-synaptic receptors. Dystrophin-expressing hippocampal neurons are key to cognitive functions such as emotions, learning and the consolidation of memories. In the context of disease-induced chronic inflammation, we have explored the role of the pleiotropic cytokine, interleukin (IL)-6 in hippocampal dysfunction using immunofluorescence, electrophysiology and metabolic measurements in dystrophic mdx mice. Hippocampal long-term potentiation (LTP) of the Schaffer collateral-CA1 projections was suppressed in mdx slices. Given the importance of mitochondria-generated ATP in synaptic plasticity, reduced maximal respiration in the CA1 region may impact upon this process. Consistent with a role for IL-6 in this observation, early LTP was suppressed in dystrophin-expressing wildtype slices exposed to IL-6. In dystrophic mdx mice, exposure to IL-6 suppressed mitochondrial-mediated basal metabolism in CA1, CA3 and DG hippocampal regions. Furthermore, blocking IL-6-mediated signalling by administering neutralising monoclonal IL-6 receptor antibodies intrathecally, normalised LTP in mdx mice. The impact of dystrophin loss from the hippocampus was associated with modified cellular bioenergetics, which underpin energy-driven processes such as the induction of LTP. The additional challenge of pathophysiological levels of IL-6 resulted in altered cellular bioenergetics, which may be key to cognitive deficits associated with the loss of dystrophin.